Effects of thyme (Thymus vulgaris L.) addition on the volatile compounds of mutton broth during boiling - Shasha Qi; Ping Zhan; Honglei Tian; Peng Wang; Xueping Ma; Kaixuan Li (Food Science and Human Wellness)
To investigate the effects of thyme (Thymus vulgaris L.) addition on the flavor modification of mutton broth during boiling, three mutton-broth samples with various thyme contents 0.06% (S1), 0.30% (S2), and 1.50% (S3) were analyzed and compared, without thyme as control (0.00%, S0). The meaty, fatty, pastoral flavor and spicy were chosen as sensory attributes to evaluate the flavor of the mutton-broth samples. Sensory results were significantly different (P < 0.001), with S2 having the optimum overall acceptability. A total of 99 volatile compounds were identified by gas chromatography-mass spectrometry, among which 19 compounds were considered as the odor-active compounds according to their odor activity values. Significant changes (P < 0.05) appeared in most volatiles in S0 with thyme addition, especially aldehydes. Free fatty acids (FFAs) were also identified, and all of them significantly increased with increased thyme (P < 0.05). Correlation analysis of odor-active compounds, FFAs, and sensory attributes through partial least squares regression (PLSR) indicated the important volatiles and FFAs remarkably contributed to the mutton broth samples, and further confirmed that the 0.30% of thyme may be a desirable addition amount for the sensory characteristics of mutton broth.